Unraveling site fidelity and residency patterns of sperm whales in the insular oceanic waters of Macaronesia - Ferreira, Rita; Steiner, Lisa; Martín, Vidal; Fusar Poli, Francesca; Dinis, Ana; Kaufmann, Manfred; Fernandez, Marc; Alves, Filipe (Frontiers in Marine Science, 2022)
Knowledge of the distribution and residency of pelagic marine megafauna, particularly deep-diving species, is scarce due to their high mobility over difficult-to-access oceanic areas and long periods underwater. However, the threatened status of many of these species, such as the sperm whale Physeter macrocephalus, increases the need to obtain quantitative data to support conservation measures. In the warm temperate waters of Macaronesia (Eastern North Atlantic), sperm whales occur year-round in a set of island systems (the Azores, Madeira, and the Canaries), mainly in social groups of females and juveniles with the occasional visits of mature males. Although it is known that they perform inter-archipelago movements, information on site fidelity and residency times is still scarce. Here, based on photographic-identification data, site fidelity and residency times of sperm whales were estimated for subareas of the Azores and the Madeira archipelagos, with a preliminary assessment for a subarea of the Canaries. The Azores and Madeira subareas presented similar proportions of individuals with recaptures (~25%), mainly inter-annual, while in the subarea of the Canaries, only <10% of the individuals were recaptured. Standardized Site Fidelity Indexes showed very low values (<0.01) for both the Azores and Madeira subareas. Lagged identification rates based on models including emigration and reimmigration estimated that an average of 44.8 individuals (SE=4.9) spent 12.9 days (SE=1.5) in the Azores before leaving for 99.1 days (SE=12.5), while 8.4 individuals (SE=16.1) spent 0.8 day (SE=6.6) in Madeira before leaving for 8.6 days (SE=6.9), with a very low mortality rate. This study i) indicates a degree of residency of about ¼ of the identified individuals for the Azores and Madeira subareas and ii) supports that these oceanic archipelagos constitute an important habitat for a Vulnerable species in the Atlantic. Moreover, it also highlights the importance of combining data from opportunistic and dedicated surveys and joint national and international efforts toward the conservation of marine megafauna.